Unnecessary Head Computed Tomography Scans: A Level 1 Trauma Teaching Experience. Issue 7 (July 2014) - Parma, Carolyn; Carney, Daniel; Grim, Rod; Bell, Ted; Shoff, Kimberly; Ahuja, Vanita
The Canadian CT Head Rule attempts to standardize the practice of obtaining head computed tomography (CT) scans in patients with minor head injury. Previous research indicates 10 to 35 per cent of CT scans performed do not meet these guidelines. The purpose of this study was to review our use of CT scans in the evaluation of mild traumatic brain injury and to identify 1) unnecessary head CT scans (UHCT); 2) variables associated with UHCT; and 3) associated costs. Using a trauma registry, inclusion criteria were age older than 18 years, Glasgow Coma Scale of 15, and at least one head CT scan. UHCTs were those without head injury, loss of consciousness, amnesia, or neurologic complaint. The proportion of patients meeting the criteria for UHCT was 24.2 per cent. Univariate analyses revealed ages 41 to 64 years, drug use, vehicular injury, and surgery within 24 hours were associated with UHCT (all P < 0.05). UHCTs were associated with higher Injury Severity Scores ( P = 0.008), ventilator days, and length of stay (all P < 0.05). An average cost of 1, 413 per CT equals 149, 778 in extra costs. This study suggests that current practices at our Level I trauma center result in UHCT. Further investigation into best practices would benefit our center by reducing costs and providing quality patient care.